2014
DOI: 10.3109/00016489.2014.885119
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of laryngotracheal separation in neurologically impaired pediatric patients

Abstract: The frequency of pneumonia treatment and that of suctioning decreased considerably after LTS. Furthermore, the respiratory condition improved at a rate of 63.19%. The SMID-MCDG score significantly reduced after LTS. No significant complications were observed and two-thirds of the patients were successfully discharged for home care after the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…All parents/caregivers agreed that LTS led to general flexibilization of care for these patients, primarily because there were smaller pulmonary complications. Hara et al, ( 3 ) assessed 21 patients submitted to LTS who presented with a significant reduction in episodes of pneumonia (3.38 versus 0.52; p<0.01) and in need of aspiration (4.0 versus 0.84; p<0.01), in which 17 patients had no episodes of pneumonia up to 6 months after surgery. ( 1 , 2 , 6 )…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All parents/caregivers agreed that LTS led to general flexibilization of care for these patients, primarily because there were smaller pulmonary complications. Hara et al, ( 3 ) assessed 21 patients submitted to LTS who presented with a significant reduction in episodes of pneumonia (3.38 versus 0.52; p<0.01) and in need of aspiration (4.0 versus 0.84; p<0.01), in which 17 patients had no episodes of pneumonia up to 6 months after surgery. ( 1 , 2 , 6 )…”
Section: Discussionmentioning
confidence: 99%
“…Our study reported a low rate of fistulas (5.4%), and all were treated by conservative approach. ( 1 3 , 6 , 8 13 )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sie ist für jeden Chirurgen eine ethisch schwere Entscheidung, da man chirurgisch normales laryngeales oder tracheales Gewebe alteriert und die Prozedur eine hohe Komplikationsrate von 58 % und Ineffizienz in 27 % hat [261]. Hara et al [262] gaben dementsprechend eine erfolgrei che laryngotracheale Separation bei zwei Drittel ihrer neurolo gisch beeinträchtigten Kinder an. Die laryngotracheale Separa tion kann rückgängig gemacht werden.…”
Section: Laryngo-tracheale Separationunclassified
“…Ethically, it is a very difficult decision for every surgeon because normal laryngeal or tracheal tissue is surgically altered and the procedure has a high complication rate of 58% and an inefficiency of 27% [ 258 ]. Correspondingly, Hara et al [ 259 ] reported on successful laryngo-tracheal separation in two thirds of their neurologically impaired pediatric patients. Laryngo-tracheal separation is a reversible procedure.…”
Section: Therapeutic Consequencesmentioning
confidence: 99%